COLOR DEVELOPMENT IN COMPLEX MODEL SYSTEM ON VARIOUS TIME AND TEMPERATURE - Agustini, Sri (Jurnal Dinamika Penelitian Industri, 2017)
The research was intended to study the development of color during heat treatment in a model real system consisted of sucrose, sweetened condensed milk, egg and margarine. Research applied was factorialcompletely randomized design with steaming time consist of 1,2,3 and 4 hours and temperatures consist of 100oC, and 110oC as treatment with 3 replication. The changes of color was investigated by using Munsell color system consist of value/lightness, hue angle, and chroma. Browning index was measured by using the absorbance of ethanol extracts at 420 nm in 40.0 mm silica. Amino acid content was observed by using HPLC. Research showed that there were negative correlation between steaming time and temperature with lightness, hue angle, chroma, and amino acid. While for TCD, and browning index indicated positive correlation.